2018
DOI: 10.3390/met8121071
|View full text |Cite
|
Sign up to set email alerts
|

Sliding Wear Behavior of Friction Couples Primarily Selected for Corrosion Resistance: Iron Boride/Iron Boride and Iron Boride/Yttria-Stabilized Zirconia

Abstract: Wear mitigation in a sliding couple is challenging if wear has to be minimized on both surfaces. In this paper, ball-on-disk testing is performed on sliding couples where both surfaces (ball and disk) are treated for wear resistance. Studied materials are pack borided H13 tool steel (ASTM A681), pack borided AISI 420 stainless steel (ASTM A276) and plasma sprayed yttria-stabilized zirconia (YSZ). Borided H13 steel exhibits a single phase Fe2B layer, while AISI 420 has a double phase layer, with FeB on the oute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…On the other hand, in the case of reinforced concrete structures, it has been demonstrated that the rebar corrosion can depend on its surface state and the passivation and anticorrosion behavior can be improved through rebar surface treatments [7]. Finally, in the case of steel, hot work sliding parts specific surface modifications must be developed for guaranteeing corrosion and wear resistance through boriding or yttria-stabilized zirconia thermal spray coating [8].…”
Section: Effect On Corrosion Behaviormentioning
confidence: 99%
“…On the other hand, in the case of reinforced concrete structures, it has been demonstrated that the rebar corrosion can depend on its surface state and the passivation and anticorrosion behavior can be improved through rebar surface treatments [7]. Finally, in the case of steel, hot work sliding parts specific surface modifications must be developed for guaranteeing corrosion and wear resistance through boriding or yttria-stabilized zirconia thermal spray coating [8].…”
Section: Effect On Corrosion Behaviormentioning
confidence: 99%
“…There is a large existing body of work on the tribological and wear properties of AISI 420 stainless steel [8,9,10,11,12,13,14,15,16,17]. Recently, D’Ans et al [8] studied the tribological and wear behaviors of the AISI 420/Fe 2 B surface layer by ball-disc tribological and wear tests. For cryogenically-treated AISI 420 steel, Prieto et al [9,10] performed frictional wear tests with grease lubrication and an argon atmosphere.…”
Section: Introductionmentioning
confidence: 99%